The scenario of obtaining initial information about the embossed surface of the facade decor element using laser scanning - Doroshenko, Yurii; Neshchadym, Vladyslav (Theory and practice of design, 2022)
The article examines the computer technology of restoration of architectural monuments, namely the process of obtaining point information for the construction of a spatial 3D model of the element of the facade. Goal. The purpose of the publication is to present an iterative scenario of complex 3D-modeling of the relief surface of the facade decor element for the purposes of restoration of architectural monuments according to laser scanning (cloud of points) with a given accuracy of reproduction of the modeling object. Methodology. Architectural elements of facade decor are classified according to scanning features. Results. Three types of decorative elements have been identified, according to scanning features. 2D-facade decor, 3D-volume decor and 4D-sculptural. Hardware 3D scanner. An example for scanning is the capital of the Corinthian order, which shows the emergence of “shaded” areas, and how to eliminate them. Scientific novelty. An algorithm for eliminating shaded areas has been developed. The error in the scanning process is investigated on the example of the sphere, and the maximum allowable scanning range. Practical significance. Restoration reproduction of elements of facade decor according to its model requires high enough accuracy, which causes adequate obtaining of primary geometric information (clouds of incidental relief surface of the element of facade decoration points). Therefore, such information should be obtained by scanning the reproduced relief surface at certain points by a special algorithm that specifies the trajectory of the laser beam and the mode of fixing the coordinates of the points. The process of obtaining qualitative initial information in the format of a point cloud, their density and the stitching process are considered.